Interactions between Manipulation Induced Pain Modulation and Conditioned Pain Modulation Analgesia - Muhsen, Ahmad Abdel Rahman Mohammad (Curtin University, 2018)
The overall objective of this thesis was to improve our understanding of two forms of endogenous analgesia induced by conditioned pain modulation and manipulation induced pain modulation. The studies presented in this thesis have shown a significant association and a comparable increase in CPM and MIPM analgesia in response to enhanced empathetic interaction and aerobic exercise. This suggests that both forms of EA are potentially mediated by a common neuro-physiological mechanism.